Performance Analysis of the Biosolar Supply Chain in Mining Industries using AHP and SCOR Models - Nazura, Is Anin; Hasibuan, Sawarni (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2025)
The shift towards renewable alternative energy has become a critical agenda for countries worldwide, including Indonesia. The Indonesian government has set a goal to reduce CO₂ emissions by 358 million tons, or 12.5% of the national emission reduction target by 2030. This study aims to design an efficient system for measuring the performance of the biodiesel supply chain in mining companies. The research methods used are the Analytical Hierarchy Process (AHP) and Supply Chain Operations Reference (SCOR) model. The SCOR model is used to create a process-based supply chain performance evaluation system, enabling companies to evaluate their supply chain activities comprehensively for monitoring, control, and communication of business goals to related functions and the supply chain. The SCOR model focuses on five dimensions: reliability, responsiveness, agility, cost, and asset management. As a structured process hierarchy, this model facilitates supply chain management and provides metrics to assess specific performance aspects in these SCOR dimensions. Initially, relevant Key Performance Indicators (KPIs) were validated using the SCOR framework, and the weighting of selected KPIs was carried out using the AHP method. Of the 42 initial indicators, 23 were selected. The results of the performance measurement for the biodiesel supply chain in mining companies showed that the highest SCOR values were for responsiveness and cost (1.00), followed by reliability (0.95), agility (0.88), and asset management (0.82).